Reducing risk in innovation : proceedings of the 15th International DSM Conference, Melbourne, Australia, 29-30 August 2013 - Scheurmann, Elke (Hanser, 2013)
Dependency and Structure Modelling (DSM) techniques support the management of complexity by focusing attention on the elements of a complex system and how they are related to each other. The DSM perspective can assist in understanding, designing and optimising complex systems - including products, processes and organisations. This volume comprises peer-reviewed papers representing state-of-the-art in DSM research and applications. The papers were presented at the 15th International DSM Conference held in August 2013 in Melbourne, Australia.